Keterlibatan Pembentuk Undang-Undang Dalam Proses Hukum Pasca Putusan Inkonstitusional Undang-Undang Cipta Kerja - Hofifah, Hofifah; Saifuddin; Misbahul Wani; Alfaenawan, Alfaenawan (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Constitutional Court Decision No. 91/PUU-XVIII/2020 provides legal certainty regarding the validity of the Job Creation Law with a conditional unconstitutional decision for two years. This means that within a period of two years, lawmakers are expected to make improvements to the Job Creation Law. If not, the law will automatically be invalid. Using a juridical-normative method, this study examines various legal products that were born after Constitutional Court Decision No. 91/PUU-XVIII/2020, as well as various challenges in the follow-up process. The results of the study show that Law No. 13 of 2022 and Law No. 6 of 2023, as a follow-up to Constitutional Court Decision No. 91/PUU-XVIII/2020, have not fully met public expectations. Law No. 13 of 2022, which was produced through a fast track legislation process, and Law No. 6 of 2023, which is an amendment to the Job Creation Law, raises questions regarding the fulfillment of the principle of meaningful public participation, which was previously identified as a problem.